Analysis of the Implementation of Development-Based Guidance and Counseling at Early Childhood Education Institutions (PAUD) in Purwakarta Regency - Yulianty, Nadya; Almira, Almira; Suci, Vidya (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This study aims to analyze and evaluate the implementation of the Guidance and Counseling program at PAUD institutions in the Purwakarta Regency area related to the planning, implementation and evaluation of Early Childhood Guidance and Counseling processes. In addition, knowing the obstacles and obstacles in the implementation of Guidance and Counseling for early childhood. The research method uses qualitative methods. The research sample was to 19 PAUD institutions in the Purwakarta Regency area. Data collection techniques and instruments: Field Study, Interview, and Observation. The data analysis used is descriptive technique. The results of the study: (1) Planning and program formulation are only based on the results of observations and not based on the results of the needs assessment. (2) The implementation of early childhood Guidance and Counseling is still not running optimally and not all are integrated in learning due to a lack of understanding of Guidance and Counseling for young children. (3) Barriers and obstacles that arise in the implementation of guidance and counseling are the lack of support from parents for the successful process of the Guidance and Counseling program and also the lack of resources and infrastructure to support the successful process of implementing early childhood guidance and counseling.